Family Environment and Portuguese Adolescents: Impact on Quality of Life and Well-Being - Fábio Botelho Guedes; Ana Cerqueira; Susana Gaspar; Tania Gaspar; Carmen Moreno; Margarida Gaspar de Matos (MDPI AG, 2022)
Background: A healthy and supportive family environment leads to more positive results regarding adolescents' development. The main objective of this study was to explore and analyze the relationship between adolescents' quality of life (QoL) and their family environment/relationship. Method: The sample was collected as part of the Health Behavior in School-aged Children 2018 study, which included 8215 adolescents, 52.7% female, with a mean age of 14.36 years (SD = 2.28). Results: Girls are more involved in family activities (such as family meals), report being treated with fairness by their parents and feel less parental pressure to get good grades. Boys have a higher perception regarding their family affluence, better family relationships and support and better QoL. Having an above-average QoL is significantly related to high family affluence, better communication with both parents, greater involvement in family activities, greater perception of help from parents regarding decision-making, greater perception of being treated with fairness by parents and less pressure from parents to get good grades, as well as a better family relationship/support. Conclusion: It is important to determine the impact that parental divorce/separation or a weak parent-child relationship can have on adolescents. It is also necessary to consider the family relationship and structure when devising strategies and public policies related to the promotion of adolescents' health and well-being.